2022
DOI: 10.3389/fimmu.2022.913024
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Protein Hydrolysates on Growth, Digestive Enzyme Activities, Protein Metabolism, and Intestinal Health of Larval Largemouth Bass (Micropterus salmoides)

Abstract: The present study was conducted to investigate the effects of dietary inclusion of protein hydrolysates on growth performance, digestive enzyme activities, protein metabolism, and intestinal health in larval largemouth bass (Micropterus salmoides). The experimental feeding trial presented in this study was based on five isonitrogenous and isolipidic diets formulated with graded inclusion levels of protein hydrolysates, and it showed that protein hydrolysates improved growth performance, reduced larval deformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 101 publications
2
21
0
Order By: Relevance
“…This was supported by a higher expression of both tnf-α and il-10 in PBM-FPH fed groups when compared to those fed PBM-based diet, and the results were comparable to fish fed the FM control diet. Dietary supplementation of FPHs provided a similar beneficial effect on inflammatory responses in the intestine of larval largemouth bass, manifested by the downregulation of pro-inflammatory cytokines ( 5-lox and il-8 ) and upregulation of anti-inflammatory cytokines ( il-10 ) ( 22 ). These authors reported that the presence of high amounts of free histidine and glycine in FPHs supressed the inflammatory response in largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was supported by a higher expression of both tnf-α and il-10 in PBM-FPH fed groups when compared to those fed PBM-based diet, and the results were comparable to fish fed the FM control diet. Dietary supplementation of FPHs provided a similar beneficial effect on inflammatory responses in the intestine of larval largemouth bass, manifested by the downregulation of pro-inflammatory cytokines ( 5-lox and il-8 ) and upregulation of anti-inflammatory cytokines ( il-10 ) ( 22 ). These authors reported that the presence of high amounts of free histidine and glycine in FPHs supressed the inflammatory response in largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported that the presence of high amounts of free histidine and glycine in FPHs supressed the inflammatory response in largemouth bass. Also, the inhibitory effects of anti-inflammatory cytokines on the expression of pro-inflammatory cytokines have been reported to be suppressed in the inflammatory response in some teleost fish ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher dietary lipid and protein contents in aquafeeds not only increase farming cost but also lead to waste and ammonia emissions. However, lower dietary lipid or protein contents could result in negative effects on fish growth performance [ 2 , 3 ]. Therefore, how to save cost and at the same time to maintain development quality has become an important and urgent issue.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin premix and mineral premix (Yuehai Brand®) by Guangdong Yuehai Feed Group Co. Ltd., Zhanjiang, China 2. Provided by Kemin AquaScience (Zhuhai, China) 3. Exchange rates are applied: $1 = ¥6:7089.…”
mentioning
confidence: 99%